Letramentos contemporâneos: as habilidades de leitura, em ambientes digitais, dos alunos de graduação - Rosana Cardoso Gondim (2018)
This master's research aims to identify and describe the reading skills in digital environments that students of the Mathematics course of a university in the Southwest of Bahia already have, which they do not have and which ones they need to develop in order to be considered literate subjects. based on the theoretical contribution of digital literacy. In order to carry out this investigation, the following hypotheses were tested: (i) students already have navigation skills, such as searching, locating and directing information, however, they have difficulties in selecting and evaluating relevant and reliable information; (ii) when reading hypertext texts, students have difficulty integrating information from various sources; (iii) students locate information, however, do not have the necessary skills to analyze and synthesize information, but simply "copy" and "paste". It is a qualitative research of descriptive and interpretative nature. The method of data collection used was the think aloud, or verbal protocol, for allowing us to verify the process of browsing, reading and producing texts while they are occurring. Students were instructed to do a task and should seek the information to answer the questions through a web-based investigation; later, they produced a ThingLink. By this method, the student was instructed to think orally and to describe all of his or her navigational path to search for the necessary information on the Web for their production. Thus, it was possible to observe and capture their search and navigation trajectory in more detail, and it is also possible to observe their abilities in digital environments to answer the following research question: what are the digital literacy skills necessary for the development of a efficient reading practice by students in digital environments that they do not yet have, which ones still need to be improved and developed, and which ones do they already have in a satisfactory way? The research was based mainly on the following theoretical assumptions: Information Technology theories, by Aragão (2004) and Barton; Lee (2015); Literature and Digital Literacy by Magda Soares (2003), Buzato (2003), Snyder (2010), Hobbs (2010) and Ribeiro (2012); Reading and Navigation, according to Buzato (2003), Coscarelli (2014, 2016), Goldman (2013), Coscarelli; Coiro (2014) and Dias; Novais (2009); Hypertext discussed by Ribeiro (2009), Coscarelli (2001, 2006, 2012), Marcuschi (2001, 2002) and others; Multimodality, discussed by Kress (1995), Kress and Van Leeuwen (2001, 2006), Van Leeuwen (2004, 2005, 2011), Lemke (2002); (2009), Coscarelli and Coiro (2014), Bigot and Rouet (2007), Kingsley and Tancock (2014), among others and Digital Letters Matrices, according to Dias and Novais (2009). Soares. As results, we found that, although the participants had in their experiences a great contact with the digital technologies, they still do not totally dominate the abilities of searching, selecting, reading and summarizing information from texts from multiple sources, regardless of the format these texts. These results provide guidance to teachers regarding students' real needs for an efficient reading in digital environments. Many teachers still feel insecure about the influence of digital technologies in the educational context, and a picture of what needs to be improved and developed regarding the skills of these students in the classroom can contribute both to their pedagogical design and to their self-confidence and this, consequently, will reflect in a more effective and meaningful teaching, which will have, as beneficiary, the student.